AN EXPERIMENTAL STUDY ON THE PERFORMANCE OF VERTICAL BASIN SOLAR STILL - Arjunan, T.V.; Sakthivel, T.G. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In the present study, a new experimental approach is proposed to enhance the performances of the conventional single slope solar still using vertical basin at inner wall surfaces. Main objectives of this study are, to increase the distilled output of solar still by utilizing heat energy available inside vertical surfaces and to find out the optimum thickness of vertical basin experimentally. The experimental system involves six identical solar stills, one of the stills is conventional and remaining stills have vertical basin with different thicknesses (3, 6,9,12 and 15 mm). Solar stills are fabricated with an effective area of 0.009 m2 and the transparent glass angle is 11Â°. The experiments were conducted on 19.02.2016 with depth of water 20 mm. The results show that (i) productivity of vertical basin solar stills are higher than the conventional still, (ii) heat loss from inner wall surfaces to outer wall surfaces are reduced considerably in vertical basin stillÂ  (iii) optimum thickness of vertical basin is 12 mm. To conclude introducing vertical basin in conventional still improves the performance of the still.